THE ELASTO-VISCOPLASTIC-TIME-DEPENDENT NATURE OF WAXY CRUDE OILS - Tarcha, B. A.; Forte, B. P. P.; Soares, E. J.; Thompson, R. L. (Revista de Engenharia Térmica, 2014)
Production in reservoirs located in deep and ultra-deep water that contain waxy crude oils faces a huge obstacle imposed by the low temperatures of the environment. When the waxy crude oil is subjected to a temperature below the Gelation Temperature, as in the case investigated in the present work, it exhibits a variety of non-Newtonian features: elasticity, plasticity, viscous effects, and time-dependency, which renders to this material a highly complex behavior. A crucial feature that is frequently ignored when the determination of the yield stress is being carried out is the timedependency nature of these materials. We demonstrate that this character has a significant impact on the measurement of the yield stress and, therefore, values obtained from a protocol that neglects time-dependency can be substantially different from a more careful procedure.